Exploring channel conflict in an emerging economy: the small retailer's perspective. Issue 10 (24th October 2017) - Satyam,; Aithal, Rajesh K.; Maurya, Harshit
Abstract : Purpose: The purpose of this paper is to explore channel conflict from the small retailer's perspective in the context of emerging economies. The study investigates the factors and probable outcomes of perceived channel conflict. Design/methodology/approach: A qualitative research design is adopted. This study involves semi-structured in-depth interviews with 14 small retailers, selected through the purposive sampling technique, in a capital city of North India. Findings: This exploratory study reveals five key reasons for channel conflict in the context of small retailers: coercive sources of power, retailer dependence, competitive intensity, retailer characteristics, and distributors' role performance. The findings also highlight channel exit and passive acceptance as two probable outcomes of perceived channel conflict. Conflict may also lead to changes in the channel structure, which may significantly affect the success of multinational firms in emerging economies. The paper concludes with a discussion and presents an agenda for further research. Originality/value: Channel conflict is a well-researched area, but the context of most existing studies has been larger retailers in developed economies. The findings of this study provide the reasons for and outcomes of the channel conflict encountered by small retailers in emerging economies. This study should be of interest to marketing managers, especially of consumer packaged goods firms, who want to succeed in emerging economies. These managers can use insights from the study to manage channel conflict in the context of small retailers.